Polymeric nanoparticles as oral delivery systems for a grape pomace extract towards the improvement of biological activities - Costa, Joana R. (2020)
Grape pomace (GP) is a major by-product from the wine industry, known for its bioactive compounds and their impact upon gastrointestinal (GI) health. However, bioaccessibility is often poor due to their degradation during digestion. This work aimed to encapsulate bioactive GP extract (GPE) into chitosan (CS) and alginate (Alg) nanoparticles (NPs) to mitigate degradation in the GI tract. Alg and CS NPs were optimized using a rotatable central composite design and NPs were characterized for their size, polydispersity, zeta potential and total phenolics (TP) association efficiency. The best formulations showed sizes ranging 523–853 nm, polydispersity indexes of 0.11–0.36, zeta potential of −15.0–14.9 mV and TP association efficiencies of 68 and 65%. FTIR confirmed that there was no formation of new chemical groups after association of the polymers with GPE. Both formulations improved the bioaccessibility of different phenolics following in vitro GI digestion, leading to in-creased antioxidant and antimicrobial activities. Moreover, the permeability of bioactive compounds through a Caco-2/HT29-MTX co-culture was reduced, suggesting a higher residence time in the intestine. Cy5.5 was used for tracking the CS NPs, which did not affect the metabolic activity of Caco-2 and HT29-MTX cells. Confocal microscopy images confirmed the adsorption of NPs to the cellular layer and suggested a reduction of the tight junction protein occludin when cells were incubated with Cy5.5-CS in solution. This study suggests that encapsulation of GPE can offer protection against along the GI tract and improve its biological activity with significant impact for oral delivery applications, including functional foods.